Out of fertile muck: the evolving narrative of nursing - Spenceley, Shannon M. (Nursing philosophy, 2004)
The ongoing debate over the appropriateness of embracing multiple research traditions in nursing is discussed, and the impacts of that debate on the development of nursing knowledge and the nature and structure of the discipline are explored. It is asserted that this previously healthy debate has become stalled between extreme positions of unbounded pluralism and critical exclusivism. The author suggests that one possible solution may lie in connecting the elements of human living, human healing, and human wholeness in an evolving narrative that crosses paradigmatic and theoretic boundaries, and reflects the unique meanings revealed in nursing practice and scholarship.